Combined Anti-Cancer Effects of Platycodin D and Sorafenib on Androgen-Independent and PTEN-Deficient Prostate Cancer - Lu, Zongliang; Song, Wei; Zhang, Yaowen; Wu, Changpeng; Zhu, Mingxing; Wang, He; Li, Na; Zhou, Yong; Xu, Hongxia (Frontiers in Oncology, 2021)
Castration-resistant (androgen-independent) and PTEN-deficient prostate cancer is a challenge in clinical practice. Sorafenib has been recommended for the treatment of this type of cancer, but is associated with several adverse effects. Platycodin D (PD) is a triterpene saponin with demonstrated anti-cancer effects and a good safety profile. Previous studies have indicated that PC3 cells (PTEN -/-, AR -/-) are more sensitive to PD than DU145 (PTEN +/+, AR -/-) and LnCaP (PTEN -/-, AR +/+) cells, suggesting that it may also be a useful treatment for castration-resistance prostate cancer. We herein investigated the effects of combining PD with sorafenib to treat PTEN-deficient prostate cancer cells. Our data show that PD promoted sorafenib-induced apoptosis and cell cycle arrest in PC3 cells. Of interest, PD only promoted the anti-cancer effects of sorafenib in Akt-positive and PTEN-negative prostate cancer cells. Mechanistic studies revealed that PD promoted p-Akt ubiquitination by increasing the p-Akt level. PD also increased the protein and mRNA expression of FOXO3a, the downstream target of Akt. Meawhile PD promoted the function of FOXO3a and increased the protein expression of Fasl, Bim and TRAIL. Interestingly, when FOXO3a expression was inhibited, the antitumor effects of both PD and sorafenib were individually inhibited, and the more potent effects of the combination treatment were inhibited. Thus, the combination of PD and sorafenib may exert potent anti-cancer effects specifically via FOXO3a. The use of Akt inhibitors or FOXO3a agonists, such as PD, may represent a promising approach for the treatment of androgen-independent and PTEN-deficient prostate cancer.